Biogeography of Argylia D. Don (Bignoniaceae): Diversification, Andean Uplift and Niche Conservatism - Glade-Vargas, Nataly S.; Rojas, Carla; Jara-Arancio, Paola; Vidal, Paula; Arroyo, Mary T. Kalin; Hinojosa, Luis Felipe (Frontiers in Plant Science, 2021)
Andean uplift and the concomitant formation of the Diagonal Arid of South America is expected to have promoted species diversification through range expansions into this novel environment. We evaluate the evolution of Argylia, a genus belonging to the Bignoniaceae family whose oldest fossil record dates back to 49.4 Ma. Today, Argylia is distributed along the Andean Cordillera, from 15°S to 38.5°S and from sea level up to 4,000 m.a.s.l. We ask whether Argylia’s current distribution is a result of a range expansion along the Andes Cordillera (biological corridor) modulated by climatic niche conservatism, considering the timing of Andean uplift (30 Ma – 5 Ma). To answer this question, we reconstructed the phylogenetic relationships of Argylia species, estimated divergence times, estimated the realized climatic niche of the genus, reconstructed the ancestral climatic niche, evaluated its evolution, and finally, performed an ancestral range reconstruction. We found strong evidence for climatic niche conservatism for moisture variables, and an absence of niche conservatism for most of the temperature variables considered. Exceptions were temperature seasonality and winter temperature. Results imply that Argylia had the capacity to adapt to extreme temperature conditions associated with the Andean uplift and the new climatic corridor produced by uplift. Ancestral range reconstruction for the genus showed that Argylia first diversified in a region where subtropical conditions were already established, and that later episodes of diversification were coeval with the of Andean uplift. We detected a second climatic corridor along the coastal range of Chile-Peru, the coastal lomas, which allowed a northward range expansion of Argylia into the hyperarid Atacama Desert. Dating suggests the current distribution and diversity of Argylia would have been reached during the Late Neogene and Pleistocene.